Counting Lymphocytes in Histopathology Images Using Connected Components - Graf, Felix; Grzegorzek, Marcin; Paulus, Dietrich (Recognizing Patterns in Signals, Speech, Images and Videos, 2010)
In this paper, a method for automatic counting of lymphocytes in histopathology images using connected components is presented. Our multi-step approach can be divided into two main parts: processing of histopathology images, and recognition of interesting regions. In the processing part, we use thresholding and morphology methods as well as connected components to improve the quality of the images for recognition. The recognition part is based on a modified template matching method. The experimental results achieved for our algorithm prove its high robustness for this kind of applications.